Phylogeny of dracunculoid nematodes (Chromadorea: Rhabditida: Spirurina: Dracunculoidea) from some Eurasian freshwater fishes - Sokolov, Sergey G.; Kalmykov, Alexander P.; Malysheva, Svetlana V. (Zootaxa, 2020)
Sets of small ribosomal DNA (SSU rDNA) and large ribosomal DNA (LSU rDNA) sequences were obtained for Philometroides moraveci Vismanis & Yunchis, 1994, Philometra kotlani (Molnár, 1969), Philometra rischta Skrjabin, 1923, Philometra cf. obturans (Prenant, 1886) (Philometridae), Sinoichthyonema amuri (Garkavi, 1972), Agrachanus scardinii (Molnár, 1966), Kalmanmolnaria intestinalis (Dogiel & Bychowsky, 1934) and Skrjabillanus tincae Shigin & Shigina, 1958 (Skrjabillanidae). Phylogenetic analysis of SSU rDNA data shows that dracunculoid nematodes are divided into two well-supported clades designated as Clade I and Clade II, respectively. Clade I includes the type species of the genus Philonema Kuitunen-Ekbaum, 1933, some species from the family Daniconematidae Moravec & Køie, 1987 and two subfamilies of skrjabillanids, Skrjabillaninae Shigin & Shigina, 1958 and Esocineminae Moravec, 2006. Clade II unites species from the families Dracunculidae Stiles, 1907, Micropleuridae Baylis & Daubney, 1926 and Philometridae Baylis & Daubney, 1926. Within the Philometridae, there are several well-supported groups of species, one of which unites freshwater Philometra spp. from the Palearctic cyprinids, identified as P. kotlani, P rischta, P. ovata (Zeder, 1803) and P. cyprinirutili (Creplin, 1825). However, the phylogenetic relationships of most philometrids are unresolved. An analysis of partial SSU and LSU rDNA sequences indicates that there is no direct phylogenetic relationship between Agrachanus Tikhomirova, 1971 (type species Skrjabillanus scardinii Molnár, 1966) and Skrjabillanus Shigin & Shigina, 1958 (type species Sk. tincae), which means that the genus Agrachanus can be resurrected. Our study confirms that Philonematinae Ivashkin, Sobolev & Khromova, 1971 should be elevated to the family rank. We formally establish the family Philonematidae Ivashkin, Sobolev & Khromova, 1971 stat. nov. We also suggest combining the superfamilies Dracunculoidea Stiles, 1907 and Camallanoidea Railliet & Henry, 1915 into the infraorder Camallanomorpha Roberts, Janovy & Nadler, 2013.